PENGARUH KOMITMEN DAN KOMPETENSI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN DAMPAKNYA TERHADAP KINERJA GURU PADA MTsN DI KOTA BANDA ACEH - Gustiawati Gustiawati; Nasir Azis; Djuraidin Ismail (Jurnal Magister Manajemen, 2018)
The purpose of this research is to know: (1) influence of commitment and competence to organization citizenship behavior (2) influence of komtmen, competence and organization citizenship behavior toward teacher performance (3) indirect influence of commitment and competence to teacher performance at MTsN In Banda Aceh through the organization citizenship behavior. The location of this study was conducted on all MTsNs in Banda Aceh City. As for the object of this research is the influence of commitment and competence to organizational citizenship behavior and its impact on teacher performance at MTsN In Banda Aceh City, the amount of population in this research is 174 employees, while the data collection technique used is census so that sample used in this study also as many as 174 respondents, while the analytical equipment used in this research is Structural Equation Modeling (SEM). The result of the research shows that commitment and competence have positive and significant influence on organization citizenship behavior, and the commitment, competence and organization citizenship behavior are positive and significant to teacher performance, then commitment and competence indirectly have positive and significant effect on teacher performance on MTsN Di Kota Banda Aceh through organization citizenship behavior